2020
DOI: 10.3390/ijms21020651
|View full text |Cite
|
Sign up to set email alerts
|

Potent and Broad but not Unselective Cleavage of Cytokines and Chemokines by Human Neutrophil Elastase and Proteinase 3

Abstract: In two recent studies we have shown that three of the most abundant human hematopoietic serine proteases—mast cell chymase, mast cell tryptase and neutrophil cathepsin G—show a highly selective cleavage of cytokines and chemokines with a strong preference for a few alarmins, including IL-18, TSLP and IL-33. To determine if this is a general pattern for many of the hematopoietic serine proteases we have analyzed the human neutrophil elastase (hNE) and human proteinase 3 (hPR-3) for their cleavage of a panel of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Many questions are still unanswered regarding the formation of MCETs and its role on MC responses to pathogens; among them, whether MCETs might restrict the inflammatory response by breaking down cytokines and chemokines, as described in NETs (147). In this context, in vitro assays showed that MC tryptase and chymase could cleave a lower number of cytokines and chemokines than neutrophil proteases (148)(149)(150). Interestingly, when combining both MC proteases, three of the most potent Th2 cytokines (thymic stromal lymphopoietin, IL-18 and IL-33) were cleaved (149), indicating that in vivo they might exert a potent negative feedback loop or a regulatory role on anti-parasitic immunity.…”
Section: Extracellular Trapsmentioning
confidence: 99%
“…Many questions are still unanswered regarding the formation of MCETs and its role on MC responses to pathogens; among them, whether MCETs might restrict the inflammatory response by breaking down cytokines and chemokines, as described in NETs (147). In this context, in vitro assays showed that MC tryptase and chymase could cleave a lower number of cytokines and chemokines than neutrophil proteases (148)(149)(150). Interestingly, when combining both MC proteases, three of the most potent Th2 cytokines (thymic stromal lymphopoietin, IL-18 and IL-33) were cleaved (149), indicating that in vivo they might exert a potent negative feedback loop or a regulatory role on anti-parasitic immunity.…”
Section: Extracellular Trapsmentioning
confidence: 99%
“…On the one hand, the release of NSP inhibitors by S. aureus prevents degradation of PSMs and other virulence factors, which could exacerbate inflammation. On the other hand, inhibition of NSP could prevent NSP-induced endogenous inflammation, since NSP have a broad cleavage profile and also cleave various endogenous molecules, thereby inducing inflammation ( 45 ). Therefore, the release of three NSP inhibitors by S. aureus could be a hint that enhanced survival of S. aureus in contact with neutrophils is also associated with a balanced or even attenuated inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…NSPs regulate inflammatory processes via several means, including proteolytic truncation of chemokines, cytokines, and growth factors to modulate their activity, activation or shedding of cell-surface receptors at the sites of inflammation, and controlling pathways of apoptosis ( Pham, 2008 ; Hahn et al, 2019 ). The recent research findings illustrate that CatG systematically degrades fibroblast growth factor-1 (FGF-1), IL-3, IL-6, IL-7, IL-15, IL-18, IL-31, and IL-33, stem cell factor (SCF), whereas NE and PR3 completely cleave cytokine ciliary neurotrophic factor (CNTF), connective tissue growth factor (CTGF), FGF-1, FGF-9, FGF-19, FMS-like tyrosine kinase 3 ligand (flt3L), granulocyte colony-stimulating factor (G-CSF), insulin-like growth factor-1 (IGF-1), IGF-2, IL-3, IL-7, IL-15, IL-16, IL-17A, IL-31, IL-33, neuregulin-1b, SCF, thymic stromal lymphopoietin (TSLP), but not IL-1-α, IL-5, IL-8, monocyte chemoattractant protein-1 (MCP-1), macrophage colony-stimulating factor (M-CSF), RANTES, TNF-α, which are resistant to proteolysis, proposing that NSPs selectively preserve a specific set of cytokines and chemokines necessary for recruitment of inflammatory cells to the sites of tissue damage or infection ( Fu et al, 2017 ; Fu et al, 2020 ). Furthermore, PR3 can promote apoptosis in aging neutrophils via an activating cleavage of procaspase-3 in the cytosol of neutrophils.…”
Section: General Aspects Of Neutrophil Serine Proteases In Inflammationmentioning
confidence: 99%